The Effect of Bureaucratic School Structure on Teachers' Job Satisfaction: The Mediator Role of the Organizational Justice - Alanoglu, Muslim; Demirtas, Zulfu (Turkish Educational Admin Research & Development Assoc, 2021)
The purpose of this study is to examine the mediating role of organizational justice in the effects of bureaucratic school structure on teachers' job satisfaction. For this, we reached 449 teachers working in the city centre of Mersin. Enabling School Structure, Organizational Justice, and Job Satisfaction Scales were used to collect the study data. Results revealed that teachers thought the schools they worked in had a moderate level of enabling bureaucratic structure and a low obstructive bureaucratic structure. A weak association was found between bureaucratic school structure dimensions and job satisfaction, while a moderate association was found between bureaucratic school structure dimensions and organizational justice. Besides, a weak association was found between job satisfaction and organizational justice. Structural equation modelling was conducted to examine the mediating role of organizational justice in the effect of bureaucratic school structure on job satisfaction. Results revealed that organizational justice acted as a mediator in the effects of enabling bureaucracy on job satisfaction. However, because the obstructive bureaucratic structure did not have any meaningful effect on organizational justice perception, it was not possible to mention its mediating effect.
Keywords: Enabling bureaucracy; Obstructive bureaucracy; Organizational justice; Job satisfaction